Volumetric spiral chemical shift imaging of hyperpolarized [2‐13c]pyruvate in a rat c6 glioma model. Issue 3 (6th May 2015) - Park, Jae Mo; Josan, Sonal; Jang, Taichang; Merchant, Milton; Watkins, Ron; Hurd, Ralph E.; Recht, Lawrence D.; Mayer, Dirk; Spielman, Daniel M.
Abstract : Purpose: MRS of hyperpolarized [2‐ 13 C]pyruvate can be used to assess multiple metabolic pathways within mitochondria as the 13 C label is not lost with the conversion of pyruvate to acetyl‐CoA. This study presents the first MR spectroscopic imaging of hyperpolarized [2‐ 13 C]pyruvate in glioma‐bearing brain. Methods: Spiral chemical shift imaging with spectrally undersampling scheme (1042 Hz) and a hard‐pulse excitation was exploited to simultaneously image [2‐ 13 C]pyruvate, [2‐ 13 C]lactate, and [5‐ 13 C]glutamate, the metabolites known to be produced in brain after an injection of hyperpolarized [2‐ 13 C]pyruvate, without chemical shift displacement artifacts. A separate undersampling scheme (890 Hz) was also used to image [1‐ 13 C]acetyl‐carnitine. Healthy and C6 glioma‐implanted rat brains were imaged at baseline and after dichloroacetate administration, a drug that modulates pyruvate dehydrogenase kinase activity. Results: The baseline metabolite maps showed higher lactate and lower glutamate in tumor as compared to normal‐appearing brain. Dichloroacetate led to an increase in glutamate in both tumor and normal‐appearing brain. Dichloroacetate‐induced %‐decrease of lactate/glutamate was comparable to the lactate/bicarbonate decrease from hyperpolarized [1‐ 13 C]pyruvate studies. Acetyl‐carnitine was observed in the muscle/fat tissue surrounding the brain. Conclusion: Robust volumetric imaging with hyperpolarized [2‐ 13 C]pyruvate and downstream products was performed in glioma‐bearing rat brains, demonstrating changes in mitochondrial metabolism with dichloroacetate. Magn Reson Med 75:973–984, 2016. © 2015 Wiley Periodicals, Inc.